PELAYANAN DAN FASILITAS WISATA PULAU PAHAWANG DI TINJAU DARI PERSPEKTIF EKONOMI ISLAM - Putri Susanthiasih; Rusliani Rusliani (Universitas Muhammadiyah Prof Dr Hamka, 2017)
The tourism sector is basically an activity related to tourism objects and tourism support activities. The development of tourism object area has multiple effects because it can encourage the accretion of various other economic activities. Tourism in Lampung, especially along the coastal Pesawaran district, has many potential attractions of the region that these are quite interesting, especially beaches, sea, an island. Nowadays in Pesawaran district, there are no marine tourism places labeled syari'ah but if the tourist attractions are already fulfilled criteria syari'ah-based, then the tourist attractions that have been classified as a syari'ah tourist place. This research is associative that is research which intends to conduct examination and measurement of problem represent attitude based on the fact. The results of this study obtained an overview of two important indicators, namely: for the services provided by the tour guide that only a man making the inconvenience of female tourists in doing diving or snorkeling. For the facilities provided Pahawang island tour of the availability of bathrooms, food and homestay are not suitable to Islamic syariat, this can be seen from the lack of clean water for ablution, food that is not guaranteed cleanness and halalness and there is no separation between homestay men and women.